The pole-to-ground fault characteristics on DC ports of distribution energy router in future distribution network. (October 2021) - Sang, Zixia; Lei, He; Fang, Rengcun; Yan, Jiong; Yang, Dongjun; Du, Zhi; Chen, Zhu; Wang, Yicong; Fan, Hua
Abstract: As the key enablers for future distribution network, the research about fault characteristic on energy router have potential to improve the operational strategies on the interaction and interconnection for micro grid. By studying the operational principles and strategies of fault characteristic of pole-to-ground fault on DC ports of full bridge circuit, the DC output voltage and current of the DC ports based on the resistor-inductor-capacitor (R-L-C) impedance of the full bridge circuit are analyzed, and the formulas on the voltage and current are derived. The influences affected by the variation of energy router operation status are recorded and discussed. Based on the formula derivation, the fault characteristic of the proposed algorithm and control strategies are validated through the numerical simulation in Saber environment.